Workshop Soft Skills Kepemimpinan: Manajemen Sarana Dan Prasarana Mahasiswa Program Studi MPI UIN Saizu Purwokerto - Dani Rizana; Novi Mayasari; Reni Suci Wahyuni (SIGMA : Jurnal Sinergi Mengabdi, 2026)
Leadership soft skills are essential competencies that university students need to prepare for organizational and professional challenges. However, leadership competencies should be supported by managerial skills, particularly in managing educational facilities and infrastructure, which contribute to organizational effectiveness. This community service program aimed to describe the implementation of a leadership soft skills workshop through facilities and infrastructure management for students of the Islamic Education Management (MPI) Study Program, Faculty of Tarbiyah and Teacher Training, UIN Prof. K.H. Saifuddin Zuhri Purwokerto. The program employed a participatory approach consisting of preparation, implementation, and evaluation stages. The workshop was conducted through lectures, interactive discussions, observation, documentation, and participant feedback, while the collected data were analyzed using descriptive qualitative analysis. The results showed that the workshop was successfully implemented and received positive responses from participants. Students actively participated in the activities, demonstrated a better understanding of leadership and facilities management concepts, and were able to identify problems and propose alternative solutions related to educational facilities management. The workshop also strengthened students' understanding of managerial competencies as an integral part of leadership soft skills. Therefore, this workshop can serve as an effective alternative for strengthening leadership soft skills among university students.